2006
DOI: 10.3844/ajassp.2006.1760.1762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ball milling times on phase formation of Mg0.7Zn0.3Fe2O4

Abstract: Mg 0.7 Zn 0.3 Fe 2 O 4 (MZF) powder was prepared by a solid-state mixed oxide using ballmilling technique. The phase identification of calcined powders was performed using X-ray diffraction technique (XRD). It has been found that MZF powders were successfully obtained for calcination conditions of 800 o C for milling times of 36 h, whereas milling times of 12 h, unreacted ZnO, Fe 2 O 3 and MgO phases (2θ ~ 54, 57 and 63) are detected from the original mixture up to 900 o C. By increasing the calcination temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Figure c,d indicates that the diameters of the ZnO spheres decreased to 150−400 nm after calcination at 500 °C for 2 h. The FESEM images in Figure e,f show more details of the surface morphology for single ZnO spheres corresponding to the sample calcined at 500 °C for 2 h. Figure g−i shows TEM images of the ZnO spheres calcined at 500 °C for 2 h. A single porous ZnO sphere results from the agglomeration of crystalline subcrystals ranging from 20 to 45 nm. It is somewhat different in size compared to the prediction of Scherrer’s equation, because the Scherrer’s equation is based on XRD patterns whereas TEM micrographs are calculated from selected areas in a sample . The diameters of the ZnO spheres decreased after calcination as a result of the removal of soluble starch and the aggregation of the nanoparticles.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Figure c,d indicates that the diameters of the ZnO spheres decreased to 150−400 nm after calcination at 500 °C for 2 h. The FESEM images in Figure e,f show more details of the surface morphology for single ZnO spheres corresponding to the sample calcined at 500 °C for 2 h. Figure g−i shows TEM images of the ZnO spheres calcined at 500 °C for 2 h. A single porous ZnO sphere results from the agglomeration of crystalline subcrystals ranging from 20 to 45 nm. It is somewhat different in size compared to the prediction of Scherrer’s equation, because the Scherrer’s equation is based on XRD patterns whereas TEM micrographs are calculated from selected areas in a sample . The diameters of the ZnO spheres decreased after calcination as a result of the removal of soluble starch and the aggregation of the nanoparticles.…”
Section: Resultsmentioning
confidence: 97%
“…It is somewhat different in size compared to the prediction of Scherrer's equation, because the Scherrer's equation is based on XRD patterns whereas TEM micrographs are calculated from selected areas in a sample. 33 The diameters of the ZnO spheres decreased after calcination as a result of the removal of soluble starch and the aggregation of the nanoparticles.…”
Section: Raman Analysismentioning
confidence: 99%
“…because of contamination problems with iron. However, the use of tungsten carbide component and inert atmosphere and /or high vacuum processes has reduced impurity levels to within acceptable limits [37]. Common drawbacks include low surface, highly poly disperse size distribution, and partially amorphous state of the powder.…”
Section: By Using Ss Cylinder Rods Single-phase Amorphous Powder Of A...mentioning
confidence: 99%
“…HEBM was used to synthesize metal powders mechanically, which led to both amorphous and nanocrystalline intermetallic compounds. Benjamin et al (1970) reported the rst application of HEBM with higher revolutions per minute (r.p.m) to synthesize new oxide dispersion-strengthened alloys [28], which is universally applicable for quick drying or wet grinding of organic and inorganic samples [29,30].…”
Section: Introductionmentioning
confidence: 99%